LENGTH-WEIGHT RELATIONSHIP AND OTHER DIMENSIONAL RELATIONSHIPS OF METAPENAEUS MONOCEROS (FABRICIUS) FROM THE KAKINADA COAST - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Information on length-weight relation of prawns is needed in studies on growth and sexual maturity and for obtaining yield estimates by analytical models. Similarly information on carapace length—total length, total length—total weight and total weight— tail relations is needed to compare data from different sources since information on catch statistics is recorded in various units depending on local marketing practices.